Alternatives to network neutrality: A South African perspective - Petrus H. Potgieter (International Telecommunications Society (ITS), 2014)
The debate on network neutrality over the past decade has evolved (in the academic sphere but not so much in public) to include sophisticated considerations of the welfare enhancing or reducing effects of mandating network neutrality. For example, in a model by Economides and Hermalin (2012) it can be shown mathematically that among what they term the discrimination schemes," it will be the case that network neutrality is welfare enhancing. Other authors, often by looking at the European market, have argued against ex ante regulation of network neutrality Crocioni (2011) and have pointed out other dangers inherent in the mandating of network neutrality Yoo (2005). The issue is in the public eye and has, at the time of writing, lead to occasional (our Internet!") street protests in various places. Similarly to Bauer and Obar (2014), this paper suggests a mix of policies and interventions might be the most appropriate way of addressing the concerns raised by activists and industry analysts in the discussion of discrimination on the last-mile network. Our preference is for an approach that can be easily understood by consumers; allows for relatively simple welfare and competition enhancing regulation and allows for the greatest possible degree of freedom for service providers to invest and to pursue their commercial interests.
Keywords: 330